Financial Management Proficiency For MSMEs - Mohammad Chaidir; Grace Yulianti; Seger Santoso; Cahyatih Kumandang (Universitas 17 Agustus 1945 Semarang, 2023)
This research investigates the financial management proficiency essential for the success of Micro, Small, and Medium Enterprises (MSMEs). The study aims to explore the strategies employed by MSMEs to effectively manage their finances and navigate challenges. The research model adopts an interpretivist approach, utilizing semi-structured interviews with MSME owners and managers. A purposive sampling technique is employed to select participants representing diverse industries and geographic locations. Data analysis involves thematic coding to identify patterns, themes, and insights regarding financial management practices. Preliminary findings suggest a variety of strategies, including budgeting, cash flow management, and strategic investment decisions, play pivotal roles in MSME success. Additionally, the study identifies common challenges faced by MSMEs in financial management, such as limited access to financial resources and lack of financial literacy. This research contributes to understanding the nuanced dynamics of financial management within the MSME sector, providing valuable insights for policymakers, practitioners, and MSME owners striving for sustainable growth and success.